2020
DOI: 10.3897/zookeys.978.55767
|View full text |Cite
|
Sign up to set email alerts
|

Ants of the Hengduan Mountains: a new altitudinal survey and updated checklist for Yunnan Province highlight an understudied insect biodiversity hotspot

Abstract: China’s Hengduan Mountain region has been considered one of the most diverse regions in the northern hemisphere. Its stunning topography with many deep valleys and impassable mountain barriers has promoted an astonishing diversification in many groups of organisms including plants, birds, mammals, and amphibians. However, the insect biodiversity in this region is still poorly known. Here, the first checklist of ant species from the Southern Hengduan Mountain region is presented, generated by sampling ant diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In explaining the extraordinary Rhododendron diversity of the region (more than 50% of the world's existing species), Irving and Hebda (1993) postulated that species inhabiting a deep valley diverged in response to recurrent glacial‐interglacial climate changes. While insect diversity in the region is largely understudied (Ji et al, 2013; Liu et al, 2020), recent studies on the distribution of plants and vertebrates confirmed the presence of a Pleistocene glacial barrier and refugia across the entire range of Hengduan‐Himalaya (Meng et al, 2015; Qiu et al, 2011; Wan et al, 2021). Most studies of biodiversity in the region have addressed the process of interspecies divergence, while the "missing link" lies in explaining the accumulation of intraspecific genetic diversity across the mountain‐valley landscape.…”
Section: Introductionmentioning
confidence: 99%
“…In explaining the extraordinary Rhododendron diversity of the region (more than 50% of the world's existing species), Irving and Hebda (1993) postulated that species inhabiting a deep valley diverged in response to recurrent glacial‐interglacial climate changes. While insect diversity in the region is largely understudied (Ji et al, 2013; Liu et al, 2020), recent studies on the distribution of plants and vertebrates confirmed the presence of a Pleistocene glacial barrier and refugia across the entire range of Hengduan‐Himalaya (Meng et al, 2015; Qiu et al, 2011; Wan et al, 2021). Most studies of biodiversity in the region have addressed the process of interspecies divergence, while the "missing link" lies in explaining the accumulation of intraspecific genetic diversity across the mountain‐valley landscape.…”
Section: Introductionmentioning
confidence: 99%
“…References. Xu (2003) ; Fontanilla et al (2019) ; He et al (2020) ; Liu et al (2020) ; Hosoishi et al (2022) .…”
Section: Taxonomymentioning
confidence: 99%
“…References. Zhou and Zheng (1997) ; Zhou (2001) ; Lin and Wu (2003) ; Zhou et al (2006) ; Terayama (2009) ; Guénard and Dunn (2012) ; Liu et al (2020) .…”
Section: Taxonomymentioning
confidence: 99%
“…Gaoligongshan runs nearly 500 km north to south between 28°30′N and 24°40′N, paralleling the China‐Myanmar border (Figure 1) and varying in elevation from 523 m above sea level to a snow cap at 5128 m. Its vegetation types range from mixed coniferous‐broadleaf forest in the north to subtropical forest in the south (Li & Li, 2020; Liu et al, 2021). The region's rugged topography has generated high species richness in plants (Xing & Ree, 2017), vertebrates (Dumbacher et al, 2011; Yang et al, 2019), and arthropods (Liu et al, 2020; Yi et al, 2021). At 28,000 km 2 (7% of the area of Yunnan), Gaoligongshan contains at least 57.5% of birds, 61% of mammals, and 23% of ant species ever reported in Yunnan.…”
Section: Introductionmentioning
confidence: 99%